Enhancing layer farm MSMEs productivity through egg grading machines and stainless cage mats - Yulinda Uswatun Kasanah; Syarif Hidayatuloh; Aulia Desy Nur Utomo (University of Merdeka Malang, 2025)
Poultry and egg farming SMEs must be empowered to enhance egg and chicken production through the development of egg-sorting equipment and tools aimed at reducing egg defects. This initiative seeks to improve the performance of micro, small, and medium enterprises (MSMEs) in the poultry sector. The implementation of sorting tools significantly alleviates the operational burden on livestock in MSMEs by accelerating the sorting process, which in turn facilitates faster product shipments. Over the long term, this can lead to a decrease in the number of sorting employees required and helps minimize egg breakage during harvesting. Moreover, the introduction of curved stainless steel cage bottoms significantly enhances egg production capacity. This innovation leads to an average reduction of 54 percent in the number of defective eggs during harvesting. Furthermore, sorting time sees an impressive average decrease of 28 percent. Currently, the average sorting time for an egg is 31.42 seconds, but with the implementation of the Automatic Egg Sorter Tool, this time is reduced to 22.6 seconds per egg, reflecting a marked improvement in efficiency.